Anaemia Preventive Practices among Pregnant Women in Central Hospital Warri, Delta State, Nigeria - Vincent Junior, Igben Onoriode; Godswill, Okoro Ogheneyebrorue; Ernest, Enemodia Oghenekevwe; Azubike, Ijeomah Trust; Omio, Irere; Bridget, Nwandu; Arhogbe, Faka Gordon; Onoriode, Gad (International Journal of Human and Health Sciences (IJHHS), 2023)
Background: Anaemia in pregnancy is among the top threats in developing countries. Several strategies against anaemia have been adopted but it still remains a major cause of maternal and infant mortality. Objective: To determine the knowledge and effectiveness of anaemia preventive practices. Methods: This is a cross-sectional, descriptive study carried out at Central Hospital Warri in Delta State, Nigeria, among 337 pregnant women seen during the antenatal clinic between July and December of 2022. A self and interviewer administered questionnaire was used for data collection. Results: The study showed no association between sociodemographic factors and anaemia in pregnancy (P>0.05); however, a high-level adherence to the anaemia preventive practices by the participants was evident. Malaria in index pregnancy was significantly associated with anaemia. Conclusion: The pregnant women had a relatively fairly good understanding and usage of anaemia preventive practices, however the effectiveness of use, the occurrence of anaemia did not affect them. International Journal of Human and Health Sciences Vol. 07 No. 04 Oct’23 Page: 314-320